INTERACTIONS OF SQUID AND SMALL PELAGIC RESOURCES IN THE ALAS STRAIT, INDONESIA - A. Ghofar (JOURNAL OF COASTAL DEVELOPMENT, 2002)
Small pelagic and squid fisheries of the Alas Strait in Indonesia are compared, to explore potential interactions  between major components caught, which may then be taken into management consideration. The data time series used for analysis were taken from major fishing harbours and landing places, and go back as far as 1970s. The small pelagic fishery in Alas Strait is mainly targeted upon squid (mostly Loligo edulis) by means of ‘jala-oras’ (payang-type) fishing, which is also used to catch small pelagic fishes during squid-off season. The small pelagic catches consist primarily of lemuru (Sardinella lemuru),  tembang (Sardinella fimbriata), layang scad (Decapterus spp), and kembung (Rastrelliger spp), which are usually taken by various pelagic fishing gears. There was a general increase in the small pelagic catches from around 4,000t in 1976 to nearly 12,000t in 1990, after which a considerable fluctuation occurred, reaching a level of 8,000t in 1999. Squid catches  increased steadily from <100t to 1,700t prior to1978 due to “jala-oras” boat motorization, but fluctuated sharply afterward. Another peak catch may be observed to approach 1,900t in 1997. During this period of large fluctuation, again, the landings  of small pelagic fishes tend to replace squid position. There is a strong indication of the existence of interaction between squid and small pelagic fisheries. In general the overall small pelagic exhibits a strong linear relationships  with a correlation coefficient, r, of 0.5270 (highly significant). More specifically their species components also shows even stronger correlations, with coefficient correlation of 0.5898, 0.6686 and 0.6358 respectively for layang, kembung and lemuru. Interactions of the species group and their  substantial implication in fisheries research and management are discussed in this paper